Penerapan Terapi Okupasi Menggambar Terhadap Perubahan Tanda Gejala Pada Pasien Dengan Gangguan Presepsi Sensori Halusinasi - Ayu Wulansari; Tri Susilowati (Jurnal Anestesi, 2023)
Background: Schizophrenia is a psychiatric disorder that affects the work of the brain. The resulting disorders can attack thoughts, perceptions, emotions, movements, and behaviors. Based on the records of the Indonesian Ministry of Health in 2019, the prevalence in Indonesia with the highest psychiatric disorders is found in Bali and Yogyakarta Provinces with each prevalence showing 11.1% and 10.4% per 1000 with people with schizophrenia / psychosis. One of the therapies to reduce anxiety in schizophrenic patients with hallucinations is environmental therapy using drawing methods. Objective: To know the results of the implementation of occupational therapy drawing on the decrease in signs and symptoms of hallucinations in patients with hallucinatory sensory perception disorders. Method: applying sensory stimulation therapy applied to 2 patients in the form of a case study. Results: After the application of occupational therapy, both respondents experienced a decrease in hallucination scores, with a total score of 14 and 5 classified as moderate hallucinations. Conclusion: Based on the data obtained, both respondents experienced a development that was originally classified as a very severe hallucination to moderate hallucination.